MhNRAMP1 From Malus hupehensis Exacerbates Cell Death by Accelerating Cd Uptake in Tobacco and Apple Calli - Zhang, Weiwei; Yue, Songqing; Song, Jianfei; Xun, Mi; Han, Mengyuan; Yang, Hongqiang (Frontiers in Plant Science, 2020)
Excessive cadmium (Cd) damages plants by causing cell death. The present study discusses the function of natural resistance-associated macrophage protein (NRAMP) on cell death caused by Cd in Malus hupehensis. MhNRAMP1 was isolated from M. hupehensis roots, and its protein was located in the cell membrane as a transmembrane protein characterized by hydrophobicity. MhNRAMP1 expression in the roots was induced by Cd stress and calcium (Ca) deficiency. MhNRAMP1 overexpression increased Cd concentration in yeasts and enhanced their sensitivity to Cd. Phenotypic comparisons of plants under Cd stress revealed that the growth of transgenic tobacco and apple calli overexpressing MhNRAMP1 was worse than that of the wild type (WT). The Cd2+ influx of transgenic tobacco roots and apple calli was higher, and the recovery time of the Cd2+ influx to a stable state in transgenic apple calli was longer than that of the WT. Cd accumulation and the percentage of apoptotic cells in transgenic lines were higher. Correspondingly, the caspase-1-like and vacuolar processing enzyme (VPE) activities and MdVPEγ expression were higher in transgenic apple calli, but the expression levels of genes that inhibit cell death were lower than those in the WT under Cd stress. Moreover, the Cd translocation from the roots to leaves was increased after MhNRAMP1 overexpression, but the Cd translocation from the leaves to seeds was not affected. These results suggest that MhNRMAP6 exacerbated Cd-induced cell death, which was accomplished by mediating Cd2+ uptake and accumulation, as well as stimulating VPE.